Synergistic treatment of sodium propionate and Sishen Pill for diarrhea mice with kidney-yang deficiency syndrome - Guo, Meifang; Di, Jiaxin; Lei, Zhijun (Frontiers in Cellular and Infection Microbiology, 2025)
ObjectiveThis study aimed to investigate the therapeutic effects of sodium propionate in combination with Sishen Pill in the treatment of diarrhea with kidney-yang deficiency syndrome in mice, with a focus on its influence on intestinal microbiota, enzyme activity, and associated therapeutic outcomes.MethodsA model of diarrhea with kidney-yang deficiency syndrome was established via adenine combined with Folium sennae administration. The model group was randomly assigned to the following treatment groups: natural recovery group, 100% Sishen Pill group, 75% Sishen Pill + 60 mg/kg sodium propionate group, 50% Sishen Pill + 120 mg/kg sodium propionate group, 25% Sishen Pill + 240 mg/kg sodium propionate group, and 480 mg/kg sodium propionate group. A variety of parameters, including general symptoms, body weight, rectal temperature, intestinal microbiota composition, microbial activity, and enzyme activity, were assessed.ResultsCompared with natural recovery group, the 480 mg/kg sodium propionate group presented significant improvements in mental state, anal temperature, fecal water content, the thymus index, and Bifidobacterium counts (p < 0.01). Compared with those in normal group, the fecal water content and Escherichia coli counts in the 100% Sishen Pill group were significantly different (p < 0.01), but no significant differences were observed compared with those in natural recovery group (p > 0.05). The 75% Sishen Pill + 60 mg/kg sodium propionate group showed improvements in mental state, food and water intake, body weight, rectal temperature, fecal water content, spleen, and thymus index, Bifidobacterium counts, total bacterial count, E. coli count, microbial activity, and lactase activity, which were close to normal levels, and significant differences were observed when compared to the natural recovery group (p < 0.01). The 50% Sishen Pill + 120 mg/kg sodium propionate group and 25% Sishen Pill + 240 mg/kg sodium propionate group also exhibited significant differences in mental status, microbial activity, and Lactobacillus count relative to those of normal group (p < 0.01). Furthermore, the 50% Sishen Pill + 120 mg/kg sodium propionate group presented significant changes in fecal water content (p < 0.01), whereas 25% Sishen Pill + 240 mg/kg sodium propionate group presented significant differences in the spleen index, total bacterial count, E. coli count, protease activity, lactase activity, and xylanase activity compared with those of normal group (p < 0.01).ConclusionThe 75% Sishen Pill + 60 mg/kg sodium propionate can improve the symptoms of kidney-yang deficiency syndrome, promote the growth and development of mice, inhibit excessive bacterial proliferation, support the growth of beneficial bacteria, and enhance intestinal enzyme activity. Its effects are superior to the use of sodium propionate or Sishen Pill alone. These results suggest that this therapeutic ratio may optimize the efficacy of Sishen Pill in the treatment of diarrhea with kidney-yang deficiency syndrome. However, further research is necessary to confirm whether this combination represents the most effective treatment regimen for this condition in mice.